DISCOURSE ANALYSIS OF TEACHER TALKS DURING ENGLISH CLASSES AT SENIOR HIGH SCHOOL METHODIST BANDA ACEH - Chairunnisa Chairunnisa (English Education Journal, 2020)
This research aimed at analyzing a spoken discourse produced by an English teacher at Senior High School Methodist Banda Aceh. The discourse analysis was done to identify the production of ideational function, interpersonal function, and textual function in the teacher talks produced by a teacher. The research method used in this study was discourse analysis which focuses on the spoken discourse to interpret deeper meaning of the spoken sentences. The respondent of this study was one English teacher at Senior High School Methodist Banda Aceh. The data collection was carried out through classroom observation and interview. The data were later analyzed by using three steps analysis. Before the process of data analysis, the data were transcribed. The results show that concerning ideational function, the teacher used mostly material process such as writing, answering, speaking, etc. Concerning interpersonal function, he mostly used declarative mood which is a mood of statement. Finally, the textual theme that he mostly used was unmarked theme, which means he frequently emphasized the subject of the sentence mostly on his students, not on adjuncts. In conclusion, the teacher used these functions to keep his students active during the teaching and learning process.